Experience report: Sexuality in adolescence with a practical and integrative approach in the Family Health Strategy (Research, Society and Development, 2023)
Introduction: Adolescence is a period of life that offers numerous challenges as it is a phase characterized, among other particularities, by the development and growth of the human being in various aspects and their perception as an individual responsible for the health-disease process.  Objective: To describe the experience of an intervention plan to integrate adolescents into the services offered by the Basic Health Unit (UBS). Methodology: This experience report was based on the practical experience of medical students working in a UBS, which took the form of an educational event focused on the comprehensive health of adolescents, with an emphasis on their sexual and mental health, with the aim of increasing their participation in the Family Health Strategy. Conclusion: As well as bringing adolescents into the health sector, the intervention encouraged the family health team to consider the most effective approaches for this public.